Contextualising Etienne de Villiers’ Ethics of Responsibility in the African context: Some recommendations - Kure , Kefas (Stellenbosch Theological Journal, 2022)
Being a South African systematic theologian, Etienne de Villiers has been involved in discourses regarding public morality with specific interest in the ethics of responsibility. In pursuing this task, his recent scholarship has resulted in proposing a contemporary Christian ethic of responsibility that addresses public moral issues. While this proposal has significant promise for engaging with issues distorting the moral fabric of most African societies, it is considered as lacking some resources for speaking to the African person critically and clearly because of its Western character. Hence, there appears to be an incompatibility with aspects of African moral and social identities in his proposal that require critical consideration of concepts more appealing to the African context. Hence, this article proposes an African (primarily Nigerian) theological engagement with de Villiers' views. The intention is to make de Villiers' work more accessible and, contextual, to the broader African ethical worldview.